1997
DOI: 10.1146/annurev.phyto.35.1.349
|View full text |Cite
|
Sign up to set email alerts
|

Rationale and Perspectives on the Development of Fungicides

Abstract: Fungicides continue to be essential for the effective control of plant diseases. New classes of fungicides with novel modes of action are being developed in the 1990s. These include the strobilurins, phenylpyrroles, anilinopyrimidines, phenoxyquinolines, and compounds that trigger defense mechanisms in the plant. For the foreseeable future, new toxophores will be identified through a process of random screening, with natural products representing a rich source of fungicide leads. Progress is being made in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
105
0
12

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(117 citation statements)
references
References 69 publications
0
105
0
12
Order By: Relevance
“…Il n'est plus certain aujourd'hui que la capacité d'invention de l'industrie agrochimique pourra dépasser la capacité d'adaptation des agents pathogènes (Leroux et al 2002). Au cours des dernières années, la réglementation en matière d'homologation de pesticides tant en Europe qu'aux États-Unis s'est tellement alourdie que seules quelques grosses compagnies agrochimiques comme Syngenta ou Bayer CropScience sont encore capables d'assumer les coûts associés à la multitude de tests toxicologiques et écotoxicologiques requis (Knight et al 1997). Outre cet aspect, la diminution progressive du nombre de matières actives disponibles sur le marché aura pour conséquence une augmentation du coût de la protection phytosanitaire, en plus d'engendrer des situations où certains agents pathogènes agressifs ne seront plus contrôlés.…”
Section: Les Sdn : Concept Et Applications En Agricultureunclassified
“…Il n'est plus certain aujourd'hui que la capacité d'invention de l'industrie agrochimique pourra dépasser la capacité d'adaptation des agents pathogènes (Leroux et al 2002). Au cours des dernières années, la réglementation en matière d'homologation de pesticides tant en Europe qu'aux États-Unis s'est tellement alourdie que seules quelques grosses compagnies agrochimiques comme Syngenta ou Bayer CropScience sont encore capables d'assumer les coûts associés à la multitude de tests toxicologiques et écotoxicologiques requis (Knight et al 1997). Outre cet aspect, la diminution progressive du nombre de matières actives disponibles sur le marché aura pour conséquence une augmentation du coût de la protection phytosanitaire, en plus d'engendrer des situations où certains agents pathogènes agressifs ne seront plus contrôlés.…”
Section: Les Sdn : Concept Et Applications En Agricultureunclassified
“…Naturally occurring plant products are important sources of antifungal compounds with low toxicity to mammals and safe to the environment which may serve as substitutes for synthetically produced fungicides. It was later suggested that these compounds might be developed either as products by themselves or used as starting point for synthesis (Knight et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…10 Direct application of fungicides remains the prevalent strategy to control these diseases. 10 However, concerns with inconsistent and declining effectiveness due to resistance, environmental impacts, animal and human toxicity and costs continue to challenge their use. Heavy use of triazole agrofungicides are linked to recent rises in human cases of invasive aspergillosis resistant to antifungal azoles.…”
Section: Introductionmentioning
confidence: 99%